Browntop Millet - Nandini, C.; Joshi, D.C.; Maharajan, Theivanayagam; Nandini, B.; Mani, Vetriventhan; Parveen, Gazala S.; Nagaraja, T.E.; Bhat, Sujata; Bhavani, P.; Divya, M.; Ceasar, Stanislaus Antony (Springer, 2025)
Browntop millet (Urochloa ramosa), an obscure member of the millet family, is gaining recognition as an essential crop for sustainable agriculture owing to its nutritional value and resilience to adverse environmental circumstances. This millet, originating from South Asia and primarily cultivated in southern India, is distinguished for its resilience on marginal soils, drought tolerance, and suitability for low-input farming systems. Browntop millet is abundant in dietary fiber, protein, calcium, iron, and antioxidants, and it contains no gluten, it can be consumed by people who have celiac disease or gluten intolerance. Its low glycemic index further augments its attractiveness as a dietary element for diabetics. Browntop millet is essential not just for nourishment but also for climate-resilient agricultural systems, as it prevents soil erosion, enhances soil fertility, and functions effectively as an intercrop. Notwithstanding its potential, cultivation and research are constrained by inadequately specified germplasm collections and insufficient genomic investigation. This chapter examines the origin of browntop millet, its domestication, agronomic techniques, nutritional importance, germplasm characterization, and possible applications, including its incorporation into value-added products such as gluten-free bread, noodles, and bioethanol. This chapter emphasizes the necessity for augmented research and breeding programs to enhance production and facilitate its incorporation into mainstream agriculture. Browntop millet, via focused initiatives, can mitigate global issues like food poverty, hunger, and climate change, establishing it as a sustainable crop for the future.